2016
DOI: 10.1177/2332858415616358
|View full text |Cite
|
Sign up to set email alerts
|

Is Kindergarten the New First Grade?

Abstract: Recent accounts suggest that accountability pressures have trickled down into the early elementary grades and that kindergarten today is characterized by a heightened focus on academic skills and a reduction in opportunities for play. This paper compares public school kindergarten classrooms between 1998 and 2010 using two large, nationally representative data sets. We show substantial changes in each of the five dimensions considered: kindergarten teachers' beliefs about school readiness, time spent on academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
289
1
11

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(339 citation statements)
references
References 36 publications
17
289
1
11
Order By: Relevance
“…Other studies have shown that teachers' priorities are context specific and might vary as a result of socio-political, cultural, or curricular factors. For example, Bassok et al (2015) have recently shown how kindergarten teachers in the US started to emphasize much more on academic competencies in the decade following the No Child Left Behind Act of 2001.…”
Section: Preschool Education In Singapore: the Learning Areas For Holmentioning
confidence: 99%
“…Other studies have shown that teachers' priorities are context specific and might vary as a result of socio-political, cultural, or curricular factors. For example, Bassok et al (2015) have recently shown how kindergarten teachers in the US started to emphasize much more on academic competencies in the decade following the No Child Left Behind Act of 2001.…”
Section: Preschool Education In Singapore: the Learning Areas For Holmentioning
confidence: 99%
“…In 1998, only 15 percent of kindergarten teachers reported that children spent three or more hours in teacher-directed, didactic, whole-class activities; in 2010, 32 percent of teachers did, doubling kindergarten children's academic work and reducing time for play. 31 Under less academic pressure than public kindergartens, most nursery schools for three-and four-year-olds held on to Dewey's and Hall's developmental paradigm. In the early days of the nursery school movement in the 1920s and 1930s, it was often all play, all of the time, as at Pratt's nursery school that the Deweys observed.…”
Section: E W E Y a N D T H E C O N T I N U I N G D I S C O U R S E mentioning
confidence: 99%
“…The study of preschool education currently has received considerable attention (e.g., Bassok, Latham, & Rorem, 2016), namely in the framework of the Russian educational reforms. However, the studies of the kindergarten teacher personality are rare in comparison to, for example, studies of required educational skills (e.g., Abdul-Haq, 2014); and they are focused primarily on traditional models of personality.…”
Section: Problem Statementmentioning
confidence: 99%
“…This work is understood as a qualified professional activity aimed at the development and education of preschool children within the educational conditions and programs provided by preschool educational institutions. However, certain work efficiency indicators of kindergarten teachers are still debatable (e.g., Adewale, 2013;Araujo, Carneiro, Cruz-Aguayo, & Schady, http://dx.doi.org/10.15405/epsbs.2017.12.20 Corresponding Author: Sergey L. Lenkov Selection and peer-review under Bassok, Latham, & Rorem, 2016). In this regard, the current study used expert assessment by professionals with extensive experience in the organization and execution of kindergarten activities.…”
Section: Conceptual Frameworkmentioning
confidence: 99%